An Alternative Pin1 Binding and Isomerization Site in the N-Terminus Domain of PSD-95 - Delgado, Jary Y. (Frontiers in Molecular Neuroscience, 2020)
Phosphorylation-dependent peptidyl-prolyl cis-trans isomerization plays key roles in cell cycle progression, the pathogenesis of cancer, and age-related neurodegeneration. Most of our knowledge about the role of phosphorylation-dependent peptidyl-prolyl cis-trans isomerization and the enzyme catalyzing this reaction, the peptidyl-prolyl isomerase (Pin1), is largely limited to proteins not present in neurons. Only a handful of examples have shown that phosphorylation-dependent peptidyl-prolyl cis-trans isomerization, Pin1 binding, or Pin1-mediated peptidyl-prolyl cis-trans isomerization regulate proteins present at excitatory synapses. In this work, I confirm previous findings showing that Pin1 binds PSD-95 and identify an alternative binding site in the phosphorylated N-terminus of the PSD-95. Pin1 associates via its WW domain with phosphorylated threonine (T19) and serine (S25) in the N-terminus domain of PSD-95 and this association alters the local conformation of PSD-95. Most importantly, I show that proline-directed phosphorylation of the N-terminus domain of PSD-95 alters the local conformation of this region. Therefore, proline-directed phosphorylation of the N-terminus of PSD-95, Pin1 association, and peptidyl-prolyl cis-trans isomerization may all play a role in excitatory synaptic function and synapse development.